Rapid assay for extrachromosomal homologous recombination in monkey cells. - Rubnitz, J (1985)
Most of the recombination assays based on the regeneration of selectable marker genes after transient infection or stable integration of DNA into mammalian cells are time consuming. We have used plasmids containing two truncated but overlapping segments of the neomycin resistance gene to rapidly quantitate and characterize the time course of extrachromosomal homologous recombination of DNA transfected into monkey COS cells. By transiently infecting cells with these recombination substrates, extracting Hirt DNA after 1 to 4 days, and transforming recombination-deficient Escherichia coli, we have shown that recombination between direct repeats occurs at frequencies of 1 to 4%. We have also used Southern blot analysis to directly characterize the recombination of this DNA in COS cells and to demonstrate that double-strand breaks in the region of homology increase recombination frequencies 10- to 50-fold.